The Effect of Blood Flow Restriction Therapy on Shoulder Function Following Shoulder Stabilization Surgery: A Case Series - John H. McGinniss; John S. Mason; Jamie B. Morris; Will Pitt; Erin M. Miller; Michael S. Crowell (North American Sports Medicine Institute, 2022)
# Background Traumatic shoulder instability is a common injury in athletes and military personnel. Surgical stabilization reduces recurrence, but athletes often return to sport before recovering upper extremity rotational strength and sport-specific abilities. Blood flow restriction (BFR) may stimulate muscle growth without the need for heavy resistance training post-surgically. # Hypothesis/Purpose To observe changes in shoulder strength, self-reported function, upper extremity performance, and range of motion (ROM) in military cadets recovering from shoulder stabilization surgery who completed a standard rehabilitation program with six weeks of BFR training. # Study Design Prospective case series # Methods Military cadets who underwent shoulder stabilization surgery completed six weeks of upper extremity BFR training, beginning post-op week six. Primary outcomes were shoulder isometric strength and patient-reported function assessed at 6-weeks, 12-weeks, and 6-months postoperatively. Secondary outcomes included shoulder ROM assessed at each timepoint and the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), the Upper Extremity Y-Balance Test (UQYBT), and the Unilateral Seated Shotput Test (USPT) assessed at the six-month follow-up. # Results Twenty cadets performed an average 10.9 BFR training sessions over six weeks. Statistically significant and clinically meaningful increases in surgical extremity external rotation strength (*p* \< 0.001; mean difference, .049; 95% CI: .021, .077), abduction strength (*p* \< 0.001; mean difference, .079; 95% CI: .050, .108), and internal rotation strength (*p \<* 0.001; mean difference, .060; CI: .028, .093) occurred from six to 12 weeks postoperatively. Statistically significant and clinically meaningful improvements were reported on the Single Assessment Numeric Evaluation (*p* \< 0.001; mean difference, 17.7; CI: 9.4, 25.9) and Shoulder Pain and Disability Index (*p* \< 0.001; mean difference, -31.1; CI: -44.2, -18.0) from six to 12 weeks postoperatively. Additionally, over 70 percent of participants met reference values on two to three performance tests at 6-months. # Conclusion While the degree of improvement attributable to the addition of BFR is unknown, the clinically meaningful improvements in shoulder strength, self-reported function, and upper extremity performance warrant further exploration of BFR during upper extremity rehabilitation. # Level of Evidence 4, Case Series